1996
DOI: 10.1172/jci118618
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a negative autocrine loop by expression of sst2 somatostatin receptor in NIH 3T3 cells.

Abstract: The somatostatin receptor subtype sst2 mediates both activation of a tyrosine phosphatase activity and inhibition of cell proliferation induced by somatostatin analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 49 publications
3
29
0
1
Order By: Relevance
“…This clone has been previously characterized. 11 As previously observed in NIH3T3/sst2 cells, sst2 expression in NIH3T3/sst2.1 cells increased DEVDase activity when compared with NIH3T3/mock cells (1.870.3-fold of NIH3T3/ mock cells; Figure 2a). These results indicated that the increase of DEVDase activity observed in sst2-expressing cells is indeed sst2-mediated and specific to sst2 expression.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…This clone has been previously characterized. 11 As previously observed in NIH3T3/sst2 cells, sst2 expression in NIH3T3/sst2.1 cells increased DEVDase activity when compared with NIH3T3/mock cells (1.870.3-fold of NIH3T3/ mock cells; Figure 2a). These results indicated that the increase of DEVDase activity observed in sst2-expressing cells is indeed sst2-mediated and specific to sst2 expression.…”
Section: Resultssupporting
confidence: 83%
“…We previously demonstrated in NIH3T3 cells stably transfected with the human sst2 cDNA (NIH3T3/sst2), that the autocrine sst2-somatostatin loop results in cell growth inhibition. 11 We therefore investigated whether sst2 induces cell death in this previously described and characterized model. 11,12 We quantified apoptosis by using the terminal deoxynucleotidyltransferase (TdT)-mediated dUTP-biotin nick end labeling (TUNEL) technique.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations